A CRITICAL APPROACH TO DEVELOPING ENGLISH SPEAKING MATERIALS BASED ON ISLAMIC VALUES - Muhammad Danil Harahap (INSPIRATION: Instructional Practices in Language Education, 2025)
English holds a strategic position in global communication, yet students' speaking skills remain limited. Widely used speaking materials often reflect external cultural values, lacking alignment with local contexts and moral education. This study aims to examine the development of English speaking materials based on Islamic values using a critical approach, focusing on both language mastery and character formation. This research employed a qualitative approach involving four English teachers and their instructional documents, including syllabi, lesson plans, and speaking activities. Data were collected through semi-structured interviews and document analysis. Findings reveal that teachers act as critical agents in developing materials through needs analysis, content selection, adaptation, value integration, and reflective evaluation. Speaking activities such as role-plays, discussions, and contextual dialogues effectively internalize Islamic values while enhancing communicative competence. A critical approach in developing Islamic value-based speaking materials creates contextual, meaningful, and ethically oriented language learning, highlighting teachers' role as reflective and critical practitioners.